Electrochemical and electron microscopic characterisation of solid-disk shungite electrodes - Sýs, Milan; Bártová, Michaela; Bartoš, Martin; Mikysek, Tomáš; Švancara, Ivan (BEST Servis, 2023)
Two different types of shungites were tested as promising electrode material for electroanalysis. Noble elite and black raw shungite stones were subjected to microscopic and elemental analysis using scanning electron microscopy and energy-dispersive X-ray spectroscopy, respectively. These stones were mechanically shaped into cylinders and then embedded into plastic tubes equipped with an electrical contact, giving rise to the appropriate solid-disk electrodes. Cyclic voltammetric measurements with pure 0.1 mol L−1 Britton Robinson buffer (pH 7) and 1 mmol L−1 potassium ferrocyanide at scan rate ranging from 20 to 300 mV s−1 were carried out to determine the corresponding double-layer capacitances, heterogeneous electron transfer rate constants, charge transfer coefficients, exchange-current densities, and electrochemically active surface areas. Compared to a commercially available glassy carbon electrode, only electrode derived from carbon rich elite shungite (90.6–94.1%) could eventually serve as several times cheaper alternative.
Elektrochemická a elektronově mikroskopická charakterizace pevných diskových šungitových elektrod
Keywords: Shungite; scanning electron microscopy; energy-dispersive X-ray spectroscopy; electrochemical kinetics; [Fe(CN)6]3−/[Fe(CN)6]4− redox couple.; Šungit; rastrovací elektronová mikroskopie; energeticky disperzní rentgenová spektroskopie; elektrochemická kinetika; [Fe(CN)6]3−/[Fe(CN)6]4− redoxní pár.